Factors Influencing the Academic Performance of Undergraduate Nursing Students at Public Sector Institution, Karachi: Factors Affecting Students’ Performance - Kumar, Vinod; Badil, .; Raja, .; Channar, Husan Bano; Khan, Ameer Ullah; Khan, Tahir; Chandio, Saran; Kumar, Ashok; Haq, Hamid ul (Pakistan BioMedical Journal, 2024)
Academic performance is a measurement of student accomplishment, which is tremendously achieved by providing a robust learning environment. Factors that hinder the incredible academic performance of nursing students include an uncomfortable learning environment, a shortage of committed faculty, and students’ financial backgrounds. Objective: To determine the factors influencing the academic performance of undergraduate nursing students at a public sector institution in Karachi. Methods: A descriptive cross-sectional study was completed at the Dow Institute of Nursing and Midwifery, Dow University of Health Sciences, Karachi. All students who were enrolled in the BSN 4 Years Degree Program were the targeted population. The calculated sample was 300 nursing students. Data were collected by adopted and validated questionnaire "Combined Survey Questionnaire". Factors influencing the academic performance of nursing students were computed in mean and standard deviation. Results: Out of total, most participants (67.7%) were unmarried, and nearly one-third (61.7%) were female. Almost (49.3%) of the study participants were between 18 and 24 years old. The highest grand mean value was obtained for teacher-related factors, whereas the lowest mean was found for home-related factors. A significant difference has been established in age (p-value=0.003), marital status (p-value=0.011), discipline (p-value=0.001), and family income (p-value=0.006) have on the academic performance of the student nurse. Conclusions: It is established that nursing students face considerable issues depending upon teacher-related factors followed by home-related factors that are linked to deterring the student’s academic performance.